2011
DOI: 10.1177/194008291100400402
|View full text |Cite
|
Sign up to set email alerts
|

Valeur de la forět des Marais Tanoé-Ehy (sudest de la COTE D'IVOIRE) pour la conservation: dimension socio-anthropologique

Abstract: Correspondances à adresser à: Inza Koné inza.kone@csrs.ci Résumé La Forêt des Marais Tanoé-Ehy (FMTE), identifiée par le Centre Suisse de Recherches Scientifiques en Côte d'Ivoire (CSRS) comme étant un site hautement prioritaire pour la conservation des primates en Afrique de l'ouest, est sujette à de fortes pressions anthropiques qui se traduisent par le braconnage, le prélèvement anarchique des ressources naturelles, l'exploitation forestière et les tentatives de défrichements agricoles. Tranchant avec les p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
7
0
9
Order By: Relevance
“…The importance of medicinal plants from PAs was clearly demonstrated by the quantitative data, as it showed that the more households depend on medicinal plants the more positive they are towards PAs. Other studies from PA benefits in an African context have yielded similar results (Hartter and Goldman, ; Zadou et al ., ). Access to most other provisioning services, is restricted through the PA management rules, and that could negatively influence people's attitudes towards PAs (Coad et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The importance of medicinal plants from PAs was clearly demonstrated by the quantitative data, as it showed that the more households depend on medicinal plants the more positive they are towards PAs. Other studies from PA benefits in an African context have yielded similar results (Hartter and Goldman, ; Zadou et al ., ). Access to most other provisioning services, is restricted through the PA management rules, and that could negatively influence people's attitudes towards PAs (Coad et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The community‐based PA management approach that was applied for the protection of the “Forêt Marécageuse de Tanoe‐Ehy (FMTE)” influenced people's perceptions of the link between PAs and wellbeing in a positive way. This can likely be attributed to the fact that, in this case, the opinions and needs of local people were integrated in the planning process from the very beginning, and outreach activities have been conducted by researchers and a local NGO (Zadou et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tout comme dans cette zone d'étude, de nombreuses études dans le monde et en Côte d'Ivoire en particulier ont mis en évidence l'usage des ressources biologiques des zones humides notamment les forêts marécageuses par les communautés riveraines pour assurer leurs obligations sociales et leur survie dans les domaines de la pharmacopée, l'alimentation, l'artisanat, la construction des habitations, agriculture ; services culturels et autres domaines (Egnankou, 2010 ;Zadou et al, 2011 ;Soro et al, 2014 ;Dargie et al, 2019).…”
Section: Discussionunclassified
“…Le Cichlidae Thysochromis ansorgii (Boulenger, 1901) est distribué en Afrique de l'Ouest des bassins côtiers de la Côte d'Ivoire, de l'Ouémé, de l'Ogun au delta du Niger et de la basse Cross (Teugels et Thys Van Den Audenaerde, 2003). Dans la forêt des marais Tanoé-Ehy (FMTE) (Côte d'Ivoire), siège d'une importante activité de pêche artisanale (Zadou et al, 2011), cette espèce fait partie des poissons figurant régulièrement dans les captures. En outre, T. ansorgii apparait comme un cichlidé pouvant intéresser le secteur de l'aquariophilie (Schacht, 2008;Arnold, 2010 Yao, 2007).Les sols sont plats, vaseux, et situés dans des basfonds plus ou moins inondés et mal drainés (Avit et al, 1999).…”
Section: Résuméunclassified